Weak Solutions of a Coupled System of Urysohn-Stieltjes Functional (Delayed) Integral Equations. (4th September 2018) - El-Sayed, A. M. A.; Al-Fadel, M. M. A.
Abstract : We study the existence of weak solutions for the coupled system of functional integral equations of Urysohn-Stieltjes type in the reflexive Banach space E . As an application, the coupled system of Hammerstien-Stieltjes functional integral equations is also studied.